1996
DOI: 10.1177/000331979604700415
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Organ Manifestations in Thromboangiitis Obliterans (Buerger's Disease) A Case Report

Abstract: Thromboangiitis obliterans (TAO) occurs almost exclusively in young male smokers. Its involvement of the small and medium-sized arteries and veins leads to ischemic complaints and/or changes in the extremities. The possibility of organ involvement is a matter of controversy. The authors report a case of TAO with multiple organ involvement, including myocardial, splenic, and cerebral infarctions; pulmonary embolisms; and probable intestinal ischemia during a twenty-three-year course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 11 publications
1
16
0
2
Order By: Relevance
“…On the other hand, documentation based on histological findings of atypical TAO, e.g., that affecting women [11,14], visceral or cerebral blood vessels [11,16,37], a diabetic patient [14] and nonsmokers [11,14] has been increasing. Therefore, there is a question of whether there is room for over-or underdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, documentation based on histological findings of atypical TAO, e.g., that affecting women [11,14], visceral or cerebral blood vessels [11,16,37], a diabetic patient [14] and nonsmokers [11,14] has been increasing. Therefore, there is a question of whether there is room for over-or underdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] In addition, TAO typically occurs with an extensive smoking history, though some cases reported symptom onset after only 2 years of tobacco use. [16] The relatively low incidence of TAO in the African American population and the historically higher incidence in males vs. females is of note. [17] While no definitive histological criteria are established, acute phase TAO is associated with inflammatory occlusive thrombi of the afflicted vessel lumen with less extensive inflammation of the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, apart from distal arteries and veins [5], visceral vessels [6, 7]and coronary arteries [8]are also occasionally affected in TAO, and involvement of cerebral arteries has been reported in cases in which cerebral artery occlusion led to infarction [9, 10]. The exact etiology of TAO is unknown.…”
Section: Discussionmentioning
confidence: 99%